Floristic diversity of grassland vegetation of the Dnepr river floodplain within the Republic of Belarus - Dobysh, Konstantin; Kulikova , Elena; Ermolenkova , Galina (Journal of the Belarusian State University. Ecology, 2024)
Based on the processing of 518 geobotanical releves of Dnieper River floodplain grassland in Belarus, 381 species of vascular plants belonging to 208 genera and 70 families have been identified. Equisetophyta is represented by 4 species, Polypodiophyta by 3 species, Pinophyta by 1 species and Magnoliophyta by 373 species. The top ten families include 228 species, which is more than half of all species of the cenoflora of Dnieper River floodplain grasslands (59,8 %). The studied cenoflora belongs to the Cyperaceae-type (Arctoboreal-East Asian) and Rosaceae-subtype (conditionally European). The features of the floristic composition of floodplain grasslands depending on the ecological conditions of their formation and mode of use are shown. The volume of the class Molinio-Arrhenatheretea cenoflora (329 species) significantly exceedsthe volume of the class Phragmito-Magnocaricetea cenoflora (210 species), which indicates a significant excess of species richness of dry and mesic meadows over wet and peaty meadows. Changes in the cenotic importance of certain plant species in the floodplain grasslands were revealed. In grasslands of the Dnieper River floodplain, 48 dominant species were recorded, of which grasses accounted for 25 species (52 %), sedges – 12 (25 %), and herbs – 11 species (23 %). The communities of the class Phragmito-Magnocaricetea are dominated by Carex acuta, Phalaroides arundinacea, Glyceria maxima, Calamagrostis canescens, Carex vulpina and others. In phytocoenoses of the class Molinio-Arrhenatheretea are dominated by Alopecurus pratensis, Galium physocarpum, Carex praecox, Poa angustifolia, Agrostis stolonifera, Poapalustris, Schedonorus pratensis, Agrostis vinealis. It was found that the share of alien plants in the studied cenoflora is 15,5% (59 species), which belong to 52 genera and 24 families. The most numerous in terms of species are families Asteraceae (14 species), Poaceae (5), Rosaceae (5) and Fabaceae (4 species). 7 invasive plant species from the «BlackBook of the Flora of Belarus» were identified: Acorus calamus, Bidens frondosa, Conyza canadensis, Echinocystis lobata, Oenothera biennis, Rumex confertus, Xanthium albinum.
Keywords: grassland vegetation; floodplain of the Dnieper river; cenoflora; taxonomic analysis; Raunkier’s life forms system; rare plant species; invasive plants